Malaria vector bionomics in Taita-Taveta County, coastal Kenya - Karisa, J; Ominde, K; Muriu, S; Munyao, V; Mwikali, K; Babu, L; Ondieki, Z; Bartilol, B; Tuwei, M; Wanjiku, C; Maia, M; Midega, J; et al. (BioMed Central, 2022)
Background Estimation of the composition and densities of mosquito species populations is crucial for monitoring the epidemiology of mosquito-borne diseases and provide information on local vectors to public health officials and policy-makers. The aim of this study was to evaluate malaria vector bionomics in ecologically distinct sites in Taita-Taveta County, Kenya. Methods Adult mosquitoes were collected using backpack aspirators and paired indoor/outdoor CDC light traps in 10 randomly selected households in six villages with distinct ecologies over a study period of 3 years. All Anopheles mosquitoes were morphotyped, and sibling species of Anopheles gambiae sensu lato (An. gambiae s.l.) were identified and separated by PCR analysis of extracted ribosomal DNA. All female anophelines were tested for sporozoite infectivity, with engorged females screened for blood-meal sources using the enzyme-linked immunosorbent assay technique. A subsample of those testing positive and those testing negative for Plasmodium in the ELISA were subjected to PCR assay. Results A total of eight different Anopheles species were collected both indoors and outdoors. Anopheles gambiae s.l. (82.6%, n = 5252) was the predominant species sensu lato, followed by Anopheles coustani sensu lato (An. coustani s.l.; (10.5%, n = 666) and Anopheles funestus sensu lato (An. funestus s.l.; 5.6%, n = 357). A subset of 683 mosquito samples representing An. gambiae s.l. (n = 580, approx. 11.0%) and An. funestus s.l. (n = 103, approx. 28.9%) were identified by molecular diagnostic assays into sibling species. The An. gambiae s.l. complex was composed of Anopheles arabiensis (62.5%, n = 363/580), An. gambiae sensu stricto (An. gambiae s.s.; 0.7%, n = 4/580), Anopheles merus (0.7%, n = 4/580) and Anopheles quadriannulatus (0.2%, n = 1/580), with the remaining samples (35.5%, n = 206/580) unamplified. Anopheles funestus s.l. was composed of An. rivulorum (14.6%, n = 15/103) and An. leesoni (11.6%, n = 12/103); the remaining samples were unamplified (73.8%, n = 76/103). A total of 981 samples were subjected to PCR analysis for malaria parasite detection; of these 16 (1.6%) were confirmed to be positive for Plasmodium falciparum. The overall human blood index was 0.13 (32/238). Conclusions Anopheles gambiae, An. funestus and An. coustani are key malaria vectors in the Taveta region of Kenya, showing concurrent indoor and outdoor transmission. All of the vectors tested showed a higher propensity for bovine and goat blood than for human blood.